Dietary phytochemicals that influence gut microbiota: Roles and actions as anti-Alzheimer agents. Issue 19 (28th October 2022) - Wang, Yi; Lim, Yau-Yan; He, Zhendan; Wong, Wing-Tak; Lai, Wing-Fu
Abstract: The last decide has witnessed a growing research interest in the role of dietary phytochemicals in influencing the gut microbiota. On the other hand, recent evidence reveals that dietary phytochemicals exhibit properties of preventing and tackling symptoms of Alzheimer's disease, which is a neurodegenerative disease that has also been linked with the status of the gut microbiota over the last decade. Till now, little serious discussions, however, have been made to link recent understanding of Alzheimer's disease, dietary phytochemicals and the gut microbiota together and to review the roles played by phytochemicals in gut dysbiosis induced pathologies of Alzheimer's disease. Deciphering these connections can provide insights into the development and future use of dietary phytochemicals as anti-Alzheimer drug candidates. This review aims at presenting latest evidence in the modulating role of phytochemicals in the gut microbiota and its relevance to Alzheimer's disease and summarizing the mechanisms behind the modulative activities. Limitations of current research in this field and potential directions will also be discussed for future research on dietary phytochemicals as anti-Alzheimer agents.